2020
DOI: 10.1016/j.idc.2019.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Antimicrobial Stewardship

Abstract: KEYWORDSAntimicrobial stewardship Role of microbiology laboratory Infectious diseases diagnosis Rapid testing Molecular panels Antibiogram Clostridium difficile KEY POINTSThe microbiology laboratory should be integrated into antibiotic stewardship programs.Rapid diagnostic technologies have the potential of decreasing time to appropriate therapy and improving patient care, and should be implemented in consultation with clinicians, clinical microbiologists, and the antibiotic stewardship team. Antibiotic stewar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Some interventions identified were public awareness campaigns [26], antimicrobial guidelines [30], professional regulation [31], restricted reimbursement [32], pay for performance, and prescription requirements [32,33]. Collaborative practice and recommen- dation acceptance by the clinical provider is also important for an antibiotic stewardship program [34] and for collaborative approaches to appropriate antimicrobial use [35]. Logan's study in 28 hospitals showed that collaborative practice in antibiotic stewardship increased days of therapy (DOT) per 1,000 patient-days of broad-spectrum antibiotics reduction from 1%-2.5% to 5%-10% [36].…”
Section: Discussionmentioning
confidence: 99%
“…Some interventions identified were public awareness campaigns [26], antimicrobial guidelines [30], professional regulation [31], restricted reimbursement [32], pay for performance, and prescription requirements [32,33]. Collaborative practice and recommen- dation acceptance by the clinical provider is also important for an antibiotic stewardship program [34] and for collaborative approaches to appropriate antimicrobial use [35]. Logan's study in 28 hospitals showed that collaborative practice in antibiotic stewardship increased days of therapy (DOT) per 1,000 patient-days of broad-spectrum antibiotics reduction from 1%-2.5% to 5%-10% [36].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced turn-around time (TAT) in either identification or susceptibility information is not sufficient to indicate the improved utility of a test, though it is an important component [ 101 ]. Other parameters include the sensitivity, specificity, type of result yielded and the confidence of the relevant clinician acting upon the result [ 102 ].…”
Section: How Should the Clinical Utility Of Novel Rapid Diagnostics Be Evaluated?mentioning
confidence: 99%
“…There is a paucity of high-quality evidence in this field, though there are numerous quasi-studies that have evaluated AMS outcomes with several incorporating a selection of clinical or process outcomes [ 45 , 103 , 104 ]. The most consistent, though not universal finding, has been that rapid technologies alone do no translate even to better AMS outcomes, let alone improved clinical outcomes, without also embedding customised AMS support strategies and this is reflected in the Infectious Diseases Society of America (IDSA) guidelines [ 45 , 52 , 101 , 105 , 106 ].…”
Section: How Should the Clinical Utility Of Novel Rapid Diagnostics Be Evaluated?mentioning
confidence: 99%
“…The DMT approach leverages a multi-disciplinary health care team, which includes the patient and medical professionals that works collaboratively to make team-based decisions with the intent to derive at an accurate and timely diagnosis. For example, the DMT approach has been useful in the timely and accurate diagnosis of active infections, permitting judicious administration of antibiotics [ 15 , 17 ]. For this example, The DMT team can include clinicians, laboratory professionals, pharmacists and infectious disease specialists, among others.…”
Section: Use Of the Diagnostic Management Team Approach To Support Diagnostic Excellencementioning
confidence: 99%